Wojna o wolność 1920, t. 1: Wyprawa kijowska, wybór i opracowanie Agnieszka Knyt, Ośrodek Karta, Warszawa 2020, ss. 263 - Koreś, Daniel (Europa Orientalis. Studia z Dziejów Europy Wschodniej i Państw Bałtyckich, 2020)
The purpose of this study is to review the book Największa klęska polskiego wywiadu. Sowiecka operacja dezinformacyjna „Trust” 1921–1927 [The greatest defeat of Polish Intelligence. Soviet disinformation operation „Trust” 1921–1927], written by Marek Świerczek. “Trust” was a cryptonym of well known secret operation of Soviet counterintelligence against Russian “white exile” and foreign intelligence services working against Soviet Russia and next USSR. An important role in this operation played Polish Military Intelligence (Second Department of Polish General Staff), being for almost six years successfully misleading by Soviet secret service GPU. As a result, Polish intelligence became not only an object of Soviet inspiration, but also – because of its mark among intelligence services working against USSR – an important “channel of inspiration” for GPU, especially to-wards European secret services. Doubtless, the Świerczek’s book is interesting and sometimes inspiring. Nevertheless, author – according to his theses – did not present any convincing evidence for one of fundamental questions of this work, i.e. existence of Soviet agency inside the Second Department of Polish General Staff.